Defluorination study of spent carbon cathode by microwave high-temperature roasting. (15th January 2022) - Zhu, Zhi; Xu, Lei; Han, Zhaohui; Liu, Jianhua; Zhang, Libo; Yang, Chuxuan; Xu, Zhangbiao; Liu, Peng
Abstract: Spent carbon cathode (SCC) produced in the process of aluminum electrolysis is a typical toxic and hazardous solid waste. Therefore, the harmless treatment of SCC is extremely important for the green development of aluminum electrolysis industry. In this paper, the microwave-assisted high-temperature roasting technology was developed to remove fluorides in SCC for recycling of this cathode. The melting point, dielectric parameter, crystalline structure, surface chemical property, elemental composition, morphological structure, carbon graphitization and surface area were characterized using thermogravimetric analysis and differential scanning calorimetry, high-temperature composite conductivity analyzer, X-ray diffraction, X-ray fluorescence, X-ray photoelectron spectroscopy, scanning electronic microscopy, transmission electron microscopy, Raman spectroscopy and isothermal N2 adsorption-desorption method. The content of fluorides in raw and treated SCC was measured by ion activity meter. The results showed that the phase of sodium fluoride and cryolite would transform from solid to liquid when the temperature was higher than 1098.5 °C, and the SCC exhibited good performance on wave absorption with the action depth of 1 cm. The SCC was mainly composed of 57.94 wt% C, 14.23 wt% NaF, 1.80 wt%, CaF2, 15.06 wt% Na3 AlF6, and 10.97 wt% Other. After treatment under microwave, the graphite carbon exhibited pitting structure and the fluorides could be effectively removed. In addition, the average layer spacing of graphite was increased from 0.34 to 0.36 nm. The defluorination of SCC could be enhanced with the increase of roasting temperature, which would attain 95.4% at 1500 °C. Compared with the traditional roasting method, the process under microwave showed more defects, which would provide a new guidance for the treatment and recycling of spent SCC. Highlights: Microwave can effectively act on SCC. Microwave is more time-saving and energy saving for traditional muffle furnace. The fluoride removal rate was as high as 93.7% when calcined at 1400 °C for 2 h. Microwave can make the graphite bond layer larger.